2002
DOI: 10.1007/s00115-002-1354-8
|View full text |Cite
|
Sign up to set email alerts
|

Entacapon zur Therapie der motorischen Fluktuationen bei idiopathischem Parkinson-Syndrom

Abstract: The treatment of idiopathic Parkinson's disease becomes rather difficult if levodopa-induced late complications such as motor fluctuations or dyskinesias occur. This prospective and open study shows that an add-on therapy with entacapone can significantly lower wearing-off and end-of-dose akinesia. This treatment is well tolerated and easy to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Recent short term studies have shown that the addition of entacapone to levodopa improves its efficacy in patients with fluctuations and reduces wearing off and end of dose akinesia. [33][34][35] Some authorities have suggested a combination of levodopa and COMT inhibitors to be used from the outset in the management of Parkinson's disease. 36 However, long term studies using COMT inhibitors with levodopa are awaited.…”
Section: Management Of Long Term Motor Complications Of Levodopamentioning
confidence: 99%
“…Recent short term studies have shown that the addition of entacapone to levodopa improves its efficacy in patients with fluctuations and reduces wearing off and end of dose akinesia. [33][34][35] Some authorities have suggested a combination of levodopa and COMT inhibitors to be used from the outset in the management of Parkinson's disease. 36 However, long term studies using COMT inhibitors with levodopa are awaited.…”
Section: Management Of Long Term Motor Complications Of Levodopamentioning
confidence: 99%